Molecularly engineered supramolecular fluorescent chemodosimeter for measuring epinephrine dynamics - Yudan Zhao; Yuxiao Mei; Zhichao Liu; Jing Sun; Yang Tian (Nature Communications)
Abstract Accurately visualizing epinephrine (EP) activity is essential for understanding its physiological functions and pathological processes in brain. However, to the best of our knowledge, reliable, rapid, and specifical measurement of EP dynamics at cellular and in vivo level hasn’t been previously reported. Herein, we report the probe for EP imaging and biosensing in neurons and living brain of freely behaving animals, based on creating a series of supramolecular fluorescent chemodosimeters through host-guest interaction. The optimized chemodosimeter enables real-time imaging and quantifying of EP with high specificity, sensitivity, signal-to-noise ratio, and rapid kinetics (~240 ms) in neurons, brain tissues and zebrafish. More significantly, we demonstrate real-time monitoring of EP in 26 regions within deep brain of freely behaving male mice, unraveling an augmented EP concentration in the amygdala, thalamus, hypothalamus, hippocampus and striatum under fear-induced stress. These findings highlight our chemodosimeter as a powerful tool for precise measurements of EP dynamics in diverse model organisms.